PENGATURAN AKTIVITAS SEBAGAI IMPLEMENTASI PIDANA KERJA SOSIAL DALAM PENJELASAN PASAL 85 UNDANG UNDANG NOMOR 1 TAHUN 2023 TENTANG KITAB UNDANG UNDANG HUKUM PIDANA - Al Faatah, Sastra Ageng; Rusdiana, Emmilia (MIZAN, Jurnal Ilmu Hukum, 2025)
The sanction of Community Service as formulated in Article 85 of Law Number 1 of 2023 concerning the Indonesian Criminal Code still contains regulatory ambiguity in determining the activities that constitute community service punishment. The purpose of this research is to determine: 1) The urgency of establishing the specific activities in the implementation of community service punishment in accordance with the explanation of Article 85 of Law Number 1 of 2023 concerning the Indonesian Criminal Code; and 2) How the determination of activities in the implementation of community service punishment is carried out in the Netherlands. This research is a normative legal study using a statutory approach. The results indicate that community service punishment in Indonesia has a clear legal basis as stipulated in Article 85 of Law Number 1 of 2023 concerning the Indonesian Criminal Code. However, there remains ambiguity in the determination of community service punishment since no implementing regulation currently exists to govern the specific activities to be performed. The explanation of Article 85 paragraph (1) only provides a general description of the places where community service may be conducted, such as hospitals, orphanages, nursing homes, schools, or other social institutions, but does not clearly specify the types of activities that must be undertaken by the offender at those locations. Therefore, implementing regulations are needed to establish standard procedures for the execution of community service punishment. The Netherlands has detailed implementing regulations supporting community service punishment, as stipulated in Articles 9 and 22c–22k of the Criminal Code of the Netherlands. The implementation of these provisions is carried out by the organization Reclassering Nederland, which could serve as a model for Indonesia in drafting its own implementing regulations to ensure that community service punishment functions effectively. Currently, the regulation of community service punishment in Indonesia relies solely on Article 85 of Law Number 1 of 2023 concerning the Indonesian Criminal Code. Therefore, implementing regulations are essential to complement existing policies and ensure that community service punishment can be effectively enforced in Indonesia.